2019
DOI: 10.5530/pj.2019.11.213
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostic study of Sphaeranthus indicus Linn.: A Review

Abstract: It is an annual, prostrate-decumbent, procumbentascending, glandular, villous, tomentose, aromatic herbs, a height of 30-60 cm. Stems are narrowly winged along with wing toothed. Leaves are sessile, 2.5-5 x1.5-2 cm, obovate-oblong, acute to rounded at tip, glandular-villous on both surfaces; apex are ABSTRACT Sphaeranthus indicus Linn. has the vernacular name of, "Mundi" and "East Indian globethistle, family Asteraceae. It is a spreading aromatic herb. It is indigenous at Rater of Chhindwara District, M.P and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The herb includes a wide variety of active pharmaceutical compounds, including eudesmenolide-7-hydroxy eudesm-4-en-6, 12-olide, 2-hydroxycostic acid, -eudesmol, ilicic acid, and methychavicol. Pure -ionone, d-cadinene, terpinene, citral, geraniol, geranyl acetate, sphaerene, indicusene, and sphaeranthol essential oils [72]. A bicyclic sesquiterpene lactone was isolated from the petroleum ether extraction of aerial portions of the Indian Composite Sphaeranthus indicus [71].…”
Section: Terpenoids and Steroidsmentioning
confidence: 99%
“…The herb includes a wide variety of active pharmaceutical compounds, including eudesmenolide-7-hydroxy eudesm-4-en-6, 12-olide, 2-hydroxycostic acid, -eudesmol, ilicic acid, and methychavicol. Pure -ionone, d-cadinene, terpinene, citral, geraniol, geranyl acetate, sphaerene, indicusene, and sphaeranthol essential oils [72]. A bicyclic sesquiterpene lactone was isolated from the petroleum ether extraction of aerial portions of the Indian Composite Sphaeranthus indicus [71].…”
Section: Terpenoids and Steroidsmentioning
confidence: 99%
“…It has also been found to be useful in the treatment of indigestion, asthma, leucoderma and dysentery. 4 A novel isoflavone glycoside from leaves and a new sesquiterpene glycoside and sphaeranthanolide were isolated from the flowers of S. indicus which was found to be an immune stimulant. The Medicinal information obtained from the tribal healers indicated that the plant is traditionally used to treat skin disease, cough and fever.…”
Section: Introductionmentioning
confidence: 99%